Runner's world train smart, run forever how to be a fit and healthy lifelong runner following the innovative 7-hour workout week - Pierce, William James 1949-; Murr, Scott 1961- (Rodale Books, 2017)
"From the experts at the Furman Institute of Running and Scientific Training (FIRST), Runner's World Train Smart, Run Forever goes beyond traditional training programs and addresses the issues that prevent runners from reaching their full potential. This book will teach you how to become a fit, fast, and healthy lifelong runner by following the authors' innovative 7-hour workout week. In this new approach, Bill Pierce and Scott Murr show how overall fitness and total body health are the secret to longevity as a runner. Runner's World Train Smart, Run Forever is appropriate for all runners, but is especially helpful if you're frustrated by injuries or looking to maintain your healthy lifestyle as you age. This book addresses the controversies surrounding the dangers of over training and the stress associated with the constant craving for faster race times. Complete with a comprehensive program to enhance overall fitness, improve race times,and support healthy aging, this book will show you how to achieve your fitness goals at any stage"--Provided by publisher.